Delivery trucks - Dickmann, Nancy (Wild about wheels (Pebble (Firm)), 2022)
"Delivery trucks carry millions of packages around the country each day. In New York City alone, 1.5 million packages are delivered every day! Young readers will learn about the types of delivery trucks, their main parts, and what they carry inside"--